2024
DOI: 10.1002/adma.202401171
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte Hydrogel‐Functionalized Photothermal Sponge Enables Simultaneously Continuous Solar Desalination and Electricity Generation Without Salt Accumulation

Lin Li,
Chaorui Xue,
Qing Chang
et al.

Abstract: Technologies that can simultaneously generate electricity and desalinate seawater are highly attractive and required to meet the increasing global demand for power and clean water. Here we develop a bifunctional solar evaporator that features continuous electric generation in seawater without salt accumulation by rational design of polyelectrolyte hydrogel‐functionalized photothermal sponge. This evaporator not only exhibits an unprecedentedly high water evaporation rate of 3.53 kg•m−2•h−1along with 98.6% sola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 65 publications
0
0
0
Order By: Relevance
“…36,37 Recent studies found that the high ionic strength of polyelectrolyte sufficiently repelled and entrapped the ions that were entering the polyelectrolyte hydrogel network, favouring better salt ion rejection. 38,39 Yet, the water evaporation rate of these hydrogels was relatively low (less than 1.7 kg m −2 h −1 under one sun irradiation), [40][41][42][43] and reached only 2.4 kg m −2 h −1 even when photothermal materials were incorporated. [44][45][46] In this work, we propose a precise surface modication strategy to produce Janus hydrogels, in which the wettability of the hydrogel's surface can be regulated by tuning the surface coverage of ultrathin Janus patches (Scheme 1).…”
Section: Xiayun Huangmentioning
confidence: 99%
See 1 more Smart Citation
“…36,37 Recent studies found that the high ionic strength of polyelectrolyte sufficiently repelled and entrapped the ions that were entering the polyelectrolyte hydrogel network, favouring better salt ion rejection. 38,39 Yet, the water evaporation rate of these hydrogels was relatively low (less than 1.7 kg m −2 h −1 under one sun irradiation), [40][41][42][43] and reached only 2.4 kg m −2 h −1 even when photothermal materials were incorporated. [44][45][46] In this work, we propose a precise surface modication strategy to produce Janus hydrogels, in which the wettability of the hydrogel's surface can be regulated by tuning the surface coverage of ultrathin Janus patches (Scheme 1).…”
Section: Xiayun Huangmentioning
confidence: 99%
“…36,37 Recent studies found that the high ionic strength of polyelectrolyte sufficiently repelled and entrapped the ions that were entering the polyelectrolyte hydrogel network, favouring better salt ion rejection. 38,39 Yet, the water evaporation rate of these hydrogels was relatively low (less than 1.7 kg m −2 h −1 under one sun irradiation), 40–43 and reached only 2.4 kg m −2 h −1 even when photothermal materials were incorporated. 44–46…”
Section: Introductionmentioning
confidence: 97%